2022
DOI: 10.1002/uog.24950
|View full text |Cite
|
Sign up to set email alerts
|

Referral scan for congenital anomalies: time to agree on indications

Abstract: Members of the SIEOG Working Group on the Obstetric Referral Scan are listed at end of manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(84 reference statements)
1
1
0
Order By: Relevance
“…Major CHD is present in 36.5% of fetuses with NT values between the 95th–99th percentile and 21.3% of fetuses with an NT ≥ 99 th percentile 11–14,26,27 . Despite this, fetal echocardiography is recommended by some guidelines for NT values > 3.0 mm or >99 th percentile 1,28–30 . Our study showed that fetuses with an NT between the 95th–99th percentile have a 10‐fold increased risk of fetal malformation, which may constitute an indication for referral for a detailed anatomy evaluation, as found by the study by Bardi et al.…”
Section: Discussionsupporting
confidence: 58%
“…Major CHD is present in 36.5% of fetuses with NT values between the 95th–99th percentile and 21.3% of fetuses with an NT ≥ 99 th percentile 11–14,26,27 . Despite this, fetal echocardiography is recommended by some guidelines for NT values > 3.0 mm or >99 th percentile 1,28–30 . Our study showed that fetuses with an NT between the 95th–99th percentile have a 10‐fold increased risk of fetal malformation, which may constitute an indication for referral for a detailed anatomy evaluation, as found by the study by Bardi et al.…”
Section: Discussionsupporting
confidence: 58%
“…Whenever possible, patients suspected of having a congenital anomaly should be referred to advanced centers for evaluation by competent personnel and de nitive diagnosis (19). This evaluation includes a detailed examination of the CNS, commonly referred to as "fetal neurosonography" (20).…”
Section: Resultsmentioning
confidence: 99%